Education of the People of Srimenanti Village Through Print and Social Media During The COVID-19 Pandemic - Adisyahputra Adisyahputra; Robby Gus Mahardika (Indonesian Journal of Community Empowerment (IJCE), 2020)
The spread of the corona virus is increasingly widespread in several areas of Indonesia including the province of the Bangka Belitung Islands. One area that is very strategic and often traversed by people that may be exposed to the spread of the corona virus is Srimenanti Village, Bangka Regency. Therefore, community service activities were carried out in Srimenanti Village which aims to educate the public about COVID-19 through social media and printed media. This activity is assisted by the team of Real Work Lectures (KKN) Universitas Bangka Belitung 2020. Education is carried out using printed media in the form of posters and banners as well as virtual media in the form of videos which are distributed to the people of Srimenanti Village and distributed through social media. The result of this activity is an increase in public understanding and awareness regarding the prevention and handling of COVID-19.